2014
DOI: 10.1007/978-3-319-13416-1_10
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder: Promoting Learner-Centric Design to Develop Mobile Games for Learning

Abstract: Abstract. Out of the project EMuRgency a game-based learning environment evolved, which trains school children in providing reanimation and cardiopulmonary resuscitation (CPR). The application gets players to act as if they were in a real case of emergency. This paper reports on a formal usability study conducted with two different groups of learners, regular learners and learners with special educational needs (SEN). With the study we compared the two groups of learners with regard to game usability and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The set of expert studies we conducted confirm our view that gamification concepts should also support intrinsic motivational factors, engagement, community-building and personalization. In line with previous results [37,[41][42][43][44][45], the designs created by our participants indicate that gamification can be helpful in education only if it is carefully selected and designed chosen according to the application scenario at hand (problem to be solved/addressed, target group, topic, domain, content).…”
Section: Discussionsupporting
confidence: 56%
“…The set of expert studies we conducted confirm our view that gamification concepts should also support intrinsic motivational factors, engagement, community-building and personalization. In line with previous results [37,[41][42][43][44][45], the designs created by our participants indicate that gamification can be helpful in education only if it is carefully selected and designed chosen according to the application scenario at hand (problem to be solved/addressed, target group, topic, domain, content).…”
Section: Discussionsupporting
confidence: 56%
“…Nine [12], [6], [46], [47], [48], [49], [50], [51] and [52] of the 50 studies indicated that there were challenges that related to a need for identifying and using instructional design guidelines to design mobile training content. Seventeen studies [6], [53], [54], [55], [44], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], and [67] mentioned challenges related to adapting and appropriating mobile learning technology to learn in a compatible way with suitable learning theories, objectives and actual training/learning needs.…”
Section: Discussionmentioning
confidence: 99%
“…That is the case shown by the example FoldagerGame, being Foldager (author's first name) + Game. NatalieCharlierGame [47] AEDApp [48] PULSE [49] BlindCPR [50] Relive [51] FoldagerGame [52] SeGTE [53] HeartRun [54][55][56][57] Staying Alive [58] LA-VIE [59] The Held Game…”
Section: Methodsmentioning
confidence: 99%
“…Tables 3.2, 3.3 and 3.4 present more detailed results. [52], [54][55][56][57], [61], [63,64], [66,67] Narrative 3 (14 %) [65], [59], [51] Relationships 4 (19 %) [54][55][56][57], [71][72][73][74][75][76][77][78], [47], [51] Players Progression 7 (33 %) [46], [52], [61], [63,64], [66,67] [46], [52], [65], [54][55][56][57], [59], [61], [63,64], [66,67], [47], [49],…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation